(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study aims to examine patient-specific factors that impact the efficacy of cognitive therapy, medication, and standard diabetes care in treating depression within the diabetic population. Depression often coexists with diabetes, posing significant challenges to effective treatment and overall health outcomes. To address this, we conducted a comprehensive review of existing literature, analyzing various patient-related elements that influence the success of interventions. Factors such as socioeconomic status, comorbidities, adherence to treatment, and individual psychological attributes play pivotal roles in determining the effectiveness of cognitive therapy, medication, and standard diabetes care. Furthermore, this research endeavors to propose evidence-based recommendations for integrated and tailored approaches that can optimize mental health outcomes while effectively managing diabetes in individuals experiencing concurrent depression. By identifying these patient-specific factors and offering tailored intervention strategies, this study aims to contribute to the enhancement of clinical practices, thereby improving the quality of life and overall well-being of diabetic individuals with comorbid depression.